Particle Formation by Supercritical Fluid Extraction and Expansion Process - Sujuan Pan; Junbo Zhou; Haiting Li; Can Quan (The Scientific World Journal)
Supercritical fluid extraction and expansion (SFEE) patented technology combines the advantages of both supercritical fluid extraction (SFE) and rapid expansion of supercritical solution (RESS) with on-line coupling, which makes the nanoparticle formation feasible directly from matrix such as Chinese herbal medicine. Supercritical fluid extraction is a green separation technology, which has been developed for decades and widely applied in traditional Chinese medicines or natural active components. In this paper, a SFEE patented instrument was firstly built up and controlled by LABVIEW work stations. Stearic acid was used to verify the SFEE process at optimized condition; via adjusting the preexpansion pressure and temperature one can get different sizes of particles. Furthermore, stearic acid was purified during the SFEE process with HPLC-ELSD detecting device; purity of stearic acid increased by 19%, and the device can purify stearic acid.